How do multidimensional energy justices work?: Specifying the role of anthropocentric and ecological justice in the acceptance of solar energy - Jeon, Sehyeok; Kim, Seoyong; Kim, Miri (Risk Analysis, 2024)
This study analyzed the acceptance of solar energy in terms of energy justice. The critical issue of energy supply, demand, and transition is a process of social redistribution of risks from old to new energy systems. The question of the appropriate distribution of risks for the energy system is closely related to energy justice. Previous studies are limited in empirically testing whether or not energy justice can contribute to the acceptance of new energy system. In addition, previous studies have heavily depended on energy justice in terms of anthropocentric type. Anthropocentric definitions of energy justice have focused primarily on the benefits and costs allocated only to humans. Such an anthropocentric view of justice lacks consideration of the value of various ecological beings. Therefore, this study aims to shed light on the role of not only four anthropocentric types of energy justices but also on for four ecological ones in the acceptance of solar energy. The analysis reveals that recognitive justice, generational justice, deep ecological justice, social ecological justice, and distributional justice positively influence the acceptance of solar energy, whereas procedural justice, restorative justice, and eco-socialist justice have no effect on it. In particular, this study found that recognitive justice moderates the effect of personal norms on acceptance of solar energy, whereas restorative justice moderates the effect of knowledge on it.
Keywords: Ecological justice; Energy; Energy justices; Energy systems; Multidimensionality; Risk perception paradigm; The acceptance of solar energy; The multidimensionality of energy justice; Theory of Planned Behavior; energy justice; risk perception paradigm; the acceptance of solar energy; the multidimensionality of energy justice; theory of planned behaviors